Cystic masses of the lateral neck: Diagnostic value comparison between fine‐needle aspiration, core‐needle biopsy, and frozen section. Issue 8 (4th April 2019) - Tabet, Paul; Saydy, Nadim; Letourneau‐Guillon, Laurent; Gologan, Olga; Bissada, Éric; Ayad, Tareck; Tabet, Jean‐Claude; Guertin, Louis; Nguyen‐Tan, Phuc Félix; Christopoulos, Apostolos
Abstract: Background: The usefulness of fine‐needle aspiration (FNA), core‐needle biopsy (CNB), and frozen section (FS) for assessing lateral cystic neck masses (LCNM) remains unclear. Methods: A retrospective review of patients presenting with a LCNM was undertaken. Results: In total, 135 patients were included. FNA had a lower sensitivity then CNB (59% vs 83%; P = .036) and FS (59% vs 93%; P = .01). FS had a better negative predictive value (NPV) when compared to FNA (92% vs 40%; P < .001) and CNB (92% vs 50%; P = .062). Positive predictive values (PPV) and sensitivities were similar among all groups. Conclusion: Given its adequate PPV (92%), FNA should be used initially on LCNM. Because of its high sensitivity, CNB should be considered if FNA is not diagnostic of malignancy. FS should always follow a CNB indicative of malignancy, because of low NPV. A diagnosis of malignancy on FNA, CNB, or FS strongly indicates presence of malignancy.